Phenotypic and genetic analysis of virulence factors in multidrug- sensitive and multidrug-resistant clinical isolates of Pseudomonas aeruginosa (Research, Society and Development, 2021)
This study aimed to correlate the pattern of antimicrobial susceptibility, phenotypic production of virulence factors, the occurrence of virulence factors genes and the clonal profile of clinical isolates of Pseudomonas aeruginosa of a tertiary hospital in Recife-PE. The 30 clinical isolates (15 multidrug-sensitive (MDS) and 15 multidrug-resistant (MDR)) were analyzed using phenotypic methods to detect virulence factors (alkaline protease, hemolysin, phospholipase C, lipase, and pigments). The detection of the aprA, lasA, lasB, plcH, and toxA genes was performed through specific PCRs, and the clonal profile was assessed using ERIC-PCR. The results revealed cephalosporins being the class eliciting the highest percentage of resistance; the MDR isolates were all resistant. Among the MDS isolates, all were sensitive to carbapenems and quinolones. The MDR isolates produced less virulence factors such as pyocyanin and lipase, and exhibited lower expression of toxA and lasA genes, whereas the MDS isolates produced less hemolysin and phospholipase C. There was no difference between the groups for alkaline protease production and aprA gene expression. All the isolates produced pyocyanin and expressed lasB and plcH genes. A great genetic diversity was found, and it was possible to observe 28 genetic profiles. Clones were present among the MDR isolates. The occurrence of virulence factors in almost all the isolates studied suggests their high level of pathogenicity, demonstrating that this pathogen is capable of accumulating numerous virulence factors, and in some cases, is associated with multidrug resistance, which makes it difficult to treat these infections.